EFEKTIVITAS PENGGUNAAN VIRTUAL LAB SEBAGAI ALAT INTERAKTIF DALAM MENINGKATKAN LITERASI SAINS DI SEKOLAH DASAR - Muhammad Irfan; Muhammad Nur Abdullah; Rizah Putrawan; A. Muh. Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of using Virtual Labs as an interactive tool to improve scientific literacy among elementary school students. The background of this research stems from the limited availability of real laboratories in elementary schools and the dominance of conventional teaching methods, which make it difficult for students to understand abstract science concepts. The research employed a mixed-method approach involving fourth-grade students at Bukit Baruga Antang Elementary School in Makassar. Quantitative data were collected through a scientific literacy questionnaire covering aspects of concept understanding, application of science, process skills, and attitudes toward science. Meanwhile, qualitative data were obtained through observations, interviews, and field notes. The findings revealed that the students’ average scientific literacy score was categorized as very high (M = 3.64), with a Customer Satisfaction Score (CSAT) of 99.09%. Students reported feeling more engaged, confident, and capable of understanding science concepts more easily when using Virtual Labs. Qualitative analysis also showed that Virtual Labs facilitated more meaningful, interactive, and engaging learning, although challenges remained in terms of device limitations and internet access. Thus, it can be concluded that Virtual Labs are effective as interactive learning media to enhance elementary students’ scientific literacy, while also offering teachers an alternative solution for teaching abstract science materials.